Ultrathin flexible lithium battery and preparation method thereof
By using a solid electrolyte layer with a thickness of 10 to 40 um and a lithium metal film of 5 to 35 um in flexible lithium batteries, the risk of lithium dendrites is solved, and an ultra-thin flexible lithium battery with high energy density and low internal resistance is achieved to avoid Short circuit phenomenon.
Patent Information
- Application Number
- CN202411379242.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-03
AI Technical Summary
Flexible lithium battery devices with thinner thickness have a high risk of lithium dendrites puncture electrolytes or diaphragms, resulting in short circuits.
The solid electrolyte layer with a thickness of 10 to 40 um is used, combined with ceramic or composite electrolyte materials, and the thickness of the electrolyte layer is adjusted by spraying or hot solvent casting. It is matched with a lithium metal film of 5 to 35 um and a positive electrode layer of 55 to 65 um to form a super Thin flexible lithium batteries ensure that the electrolyte layer is not easily pierced while maintaining low internal resistance.
It effectively avoids the risk of short circuit caused by lithium dendrites puncture, and at the same time ensures the high energy density and safety performance of ultra-thin flexible lithium batteries.
Smart Images

Figure CN119253021A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy, and in particular to lithium batteries. Background Art
[0002] As the market penetration of electric vehicles increases, liquid lithium-ion batteries have been criticized by consumers for their safety hazards, low energy density, and single shape. This is also the development dilemma faced by liquid lithium-ion power batteries. Therefore, liquid lithium-ion batteries urgently need to be updated. In such an environment, the concept of solid-state batteries came into being. Solid-state batteries not only have higher energy density, but also use safer solid electrolytes in solid-state batteries to replace traditional flammable and explosive liquid electrolytes, which have higher safety performance. In addition, solid-state batteries can introduce lithium metal anodes with lower density and higher specific capacity (theoretical specific capacity 3860mAh / g, carbon-based graphite material 372mAh / g); ensure that solid-state batteries have higher energy density. After the lithium metal anode is separated from the flammable and explosive liquid electrolyte environment, the safety hazards brought by lithium dendrites are reduced, but for thinner flexible lithium battery devices, there is still a high risk of lithium dendrites piercing the electrolyte or diaphragm and causing short circuits. Summary of the invention
[0003] The embodiments of the present application provide an ultra-thin flexible lithium battery and a preparation method and application thereof, so as to solve the technical problem that there is a risk of lithium dendrites piercing the electrolyte or the diaphragm in thin flexible lithium battery devices.
[0004] In a first aspect, an embodiment of the present application provides an ultra-thin flexible lithium battery, wherein the ultra-thin flexible lithium battery comprises:
[0005] Positive electrode current collector;
[0006] positive electrode layer;
[0007] A solid electrolyte layer, wherein the thickness of the solid electrolyte layer is 10 to 40 μm;
[0008] A negative electrode layer, wherein the material of the negative electrode layer is lithium metal;
[0009] Negative electrode current collector.
[0010] In some embodiments of the present application, the solid electrolyte is a ceramic electrolyte or a composite electrolyte.
[0011] In some embodiments of the present application, the ceramic electrolyte is at least one of lithium titanium aluminum phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium titanium oxide, lithium phosphorus sulfur chloride, and lithium germanium phosphorus sulfur.
[0012] In some embodiments of the present application, the material of the composite electrolyte includes the ceramic electrolyte and further includes at least one of polyethylene oxide, polyvinyl alcohol, and polyvinylidene fluoride.
[0013] In some embodiments of the present application, the negative electrode layer is a lithium metal film, and the thickness of the lithium metal film is 5 to 35 um; and / or,
[0014] The positive electrode active material of the positive electrode layer is at least one of lithium cobalt oxide, ternary positive electrode material, lithium nickel manganese oxide, lithium-rich manganese-based material, lithium titanate, sodium vanadium fluorophosphate, sodium vanadium phosphate, and Prussian blue; and / or,
[0015] The thickness of the positive electrode layer is 55 to 65 um; and / or,
[0016] The positive electrode current collector is a composite aluminum foil current collector; and / or,
[0017] The thickness of the positive electrode current collector is 9 to 12 um; and / or,
[0018] The negative electrode current collector is any one of copper foil, composite copper foil current collector and conductive carbon paper; and / or,
[0019] The thickness of the negative electrode current collector is 6-10 um.
[0020] In a second aspect, an embodiment of the present application provides a method for preparing the ultra-thin flexible lithium battery according to any embodiment of the first aspect, the preparation method comprising the following steps:
[0021] Providing a positive electrode active material, a binder, and a conductive agent, and uniformly mixing the positive electrode active material, the binder, and the conductive agent to obtain a positive electrode material;
[0022] Disposing the positive electrode material on the positive electrode current collector to form a positive electrode layer;
[0023] After a solid electrolyte is disposed on the positive electrode layer, the solid electrolyte is subjected to a roll-pressing process to obtain a solid electrolyte layer;
[0024] Using metallic lithium as material to prepare a negative electrode layer on a negative electrode current collector;
[0025] The negative electrode layer is laminated to the solid electrolyte layer to obtain the ultra-thin flexible lithium battery.
[0026] In some embodiments of the present application, the positive electrode active material, the binder, and the conductive agent are mixed uniformly, and the mass ratio of the positive electrode active material, the binder, and the conductive agent is 96:2:2.
[0027] In some embodiments of the present application, the positive electrode material is disposed on the positive electrode current collector by any one of spraying, deposition, and coating.
[0028] In some embodiments of the present application, a solid electrolyte is disposed on the positive electrode layer, and the solid electrolyte is disposed on the positive electrode layer by a first method or a second method.
[0029] The first method comprises the following steps:
[0030] Mixing the solid electrolyte with a solvent to obtain an electrolyte slurry;
[0031] The electrolyte slurry is sprayed onto the positive electrode layer, and the thickness of the solid electrolyte is regulated by controlling the number of spraying times.
[0032] The second method comprises the following steps:
[0033] Mixing the solid electrolyte with a solvent to obtain an electrolyte slurry;
[0034] The electrolyte slurry is coated on the positive electrode layer by hot solvent casting, and the thickness of the solid electrolyte is regulated by scraping the solid electrolyte.
[0035] In some embodiments of the present application, the preparation of the negative electrode layer on the negative electrode current collector using metallic lithium as the material is implemented by the third method or the fourth method.
[0036] The third method comprises the following steps:
[0037] The lithium metal is melted and applied to the surface of the negative electrode current collector.
[0038] The fourth method comprises the following steps:
[0039] Lithium metal is deposited on the surface of the negative electrode current collector by vacuum evaporation.
[0040] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0041] The ultra-thin flexible lithium battery provided in the embodiment of the present application sets the thickness of the solid electrolyte layer to 10 to 40 um. The solid electrolyte layer has sufficient thickness to effectively avoid being pierced by lithium dendrites and causing a battery short circuit, while also ensuring that the internal resistance of the ultra-thin flexible lithium battery is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.
[0043] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0044] Figure 1 A schematic diagram of a process for preparing an ultra-thin flexible lithium battery provided in an embodiment of the present application;
[0045] Figure 2 A charge and discharge curve diagram of the ultra-thin flexible lithium battery provided in Comparative Example 2 of the present application;
[0046] Figure 3 The AC impedance spectrum of the ultra-thin flexible lithium battery provided in Example 1 and Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0048] Unless otherwise specified, the terms used herein should be understood as commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which this application belongs. In the event of a conflict, this specification takes precedence.
[0049] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0050] Existing thinner flexible lithium battery devices have the risk of lithium dendrites piercing the electrolyte or separator.
[0051] The technical solution provided by the embodiments of the present application is to solve the above technical problems, and the overall idea is as follows:
[0052] In a first aspect, an embodiment of the present application provides an ultra-thin flexible lithium battery, wherein the ultra-thin flexible lithium battery comprises:
[0053] Positive electrode current collector;
[0054] positive electrode layer;
[0055] A solid electrolyte layer, wherein the thickness of the solid electrolyte layer is 10 to 40 μm;
[0056] A negative electrode layer, wherein the material of the negative electrode layer is lithium metal;
[0057] Negative electrode current collector.
[0058] The present application sets the thickness of the solid electrolyte layer to 10 to 40 um, so that the solid electrolyte layer has sufficient thickness to effectively avoid being pierced by lithium dendrites and causing a short circuit in the battery, while also ensuring that the internal resistance of the ultra-thin flexible lithium battery is low.
[0059] In some embodiments of the present application, the solid electrolyte is a ceramic electrolyte or a composite electrolyte.
[0060] It is easy to understand that composite electrolytes generally refer to composites of polymer electrolytes and ceramic electrolytes.
[0061] In some embodiments of the present application, the ceramic electrolyte is at least one of lithium titanium aluminum phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium titanium oxide, lithium phosphorus sulfur chloride, and lithium germanium phosphorus sulfur.
[0062] In some embodiments of the present application, the material of the composite electrolyte includes the ceramic electrolyte and further includes at least one of polyethylene oxide, polyvinyl alcohol, and polyvinylidene fluoride.
[0063] In some embodiments of the present application, the negative electrode layer is a lithium metal film, and the thickness of the lithium metal film is 5 to 35 um; and / or,
[0064] The positive electrode active material of the positive electrode layer is at least one of lithium cobalt oxide, ternary positive electrode material, lithium nickel manganese oxide, lithium-rich manganese-based material, lithium titanate, sodium vanadium fluorophosphate, sodium vanadium phosphate, and Prussian blue; and / or,
[0065] The thickness of the positive electrode layer is 55-65 um; and / or,
[0066] The positive electrode current collector is a composite aluminum foil current collector; and / or,
[0067] The thickness of the positive electrode current collector is 9 to 12 um; and / or,
[0068] The negative electrode current collector is any one of copper foil, composite copper foil current collector and conductive carbon paper; and / or,
[0069] The thickness of the negative electrode current collector is 6-10 um.
[0070] The beneficial effect of the thickness of the lithium metal film being 5 to 35 um is that it can ensure that the ultra-thin flexible lithium battery has better flexibility and that the overall thickness of the lithium metal film is relatively uniform.
[0071] As an example, the thickness of the lithium metal film may be 5um, 10um, 15um, 20um, 25um, 30um, or 35um.
[0072] It is easy to understand that the beneficial effect of the thickness of the positive electrode layer being 55 to 65 um is that the uniformity and continuity of the positive electrode layer are ensured while the flexibility of the ultra-thin flexible lithium battery is increased as much as possible.
[0073] As an example, the thickness of the positive electrode layer may be 55um, 57um, 59um, 61um, 63um, or 65um.
[0074] It is easy to understand that the beneficial effect of the thickness of the positive electrode current collector being 9 to 12 um is to increase the flexibility of the ultra-thin flexible lithium battery as much as possible on the basis of ensuring the mechanical strength of the positive electrode current collector itself.
[0075] As an example, the thickness of the positive electrode current collector may be 9 um, 10 um, 11 um, or 12 um.
[0076] It is easy to understand that the beneficial effect of the thickness of the negative electrode current collector being 6 to 10 um is to increase the flexibility of the ultra-thin flexible lithium battery as much as possible on the basis of ensuring the mechanical strength of the negative electrode current collector itself.
[0077] As an example, the thickness of the negative electrode current collector may be 6um, 7um, 8um, 9um, or 10um.
[0078] In a second aspect, an embodiment of the present application provides a method for preparing the ultra-thin flexible lithium battery according to any embodiment of the first aspect, the preparation method comprising the following steps:
[0079] S1: providing a positive electrode active material, a binder, and a conductive agent, and uniformly mixing the positive electrode active material, the binder, and the conductive agent to obtain a positive electrode material;
[0080] S2: placing the positive electrode material on the positive electrode current collector to form a positive electrode layer;
[0081] S3: after arranging a solid electrolyte on the positive electrode layer, rolling the solid electrolyte to obtain a solid electrolyte layer;
[0082] S4: preparing a negative electrode layer on a negative electrode current collector using metallic lithium as a material;
[0083] S5: Laminating the negative electrode layer and the solid electrolyte layer to obtain the ultra-thin flexible lithium battery.
[0084] It is easy to understand that the conductive agent can be selected from at least one of Ketjen black, carbon nanotubes, nanocarbon fibers, graphene, composite conductive agents, and organic conductive agents.
[0085] It is easy to understand that the binder can be selected from at least one of polytetrafluoroethylene, polyvinylidene fluoride, carboxylated polyvinylidene fluoride, polyacrylic acid, polyvinyl alcohol, sodium alginate, polyacrylamide, and polyimide.
[0086] In some embodiments of the present application, the positive electrode active material, the binder, and the conductive agent are mixed uniformly, and the mass ratio of the positive electrode active material, the binder, and the conductive agent is 96:2:2.
[0087] The beneficial effect of the mass ratio of the positive electrode active material, the binder and the conductive agent being 96:2:2 is that the energy density of the positive electrode material can be increased as much as possible while ensuring the molding ability and electrical conductivity of the positive electrode material.
[0088] In some embodiments of the present application, the positive electrode material is disposed on the positive electrode current collector by any one of spraying, deposition, and coating.
[0089] In some embodiments of the present application, a solid electrolyte is disposed on the positive electrode layer, and the solid electrolyte is disposed on the positive electrode layer by a first method or a second method.
[0090] The first method comprises the following steps:
[0091] S311: mixing the solid electrolyte with a solvent to obtain an electrolyte slurry;
[0092] S312: spraying the electrolyte slurry onto the positive electrode layer, and regulating the thickness of the solid electrolyte by controlling the number of spraying times.
[0093] The second method comprises the following steps:
[0094] S321: mixing the solid electrolyte with a solvent to obtain an electrolyte slurry;
[0095] S322: applying the electrolyte slurry onto the positive electrode layer by hot solvent casting, and regulating the thickness of the solid electrolyte by scraping the solid electrolyte.
[0096] It is easy to understand that regulating the thickness of the solid electrolyte is to regulate the thickness of the solid electrolyte layer. In some embodiments, each spraying can increase the thickness of the solid electrolyte layer by at least 10 um. In some embodiments, each scraping can reduce the thickness of the solid electrolyte layer by at least 5 um.
[0097] It is easy to understand that the solvent can be selected from at least one of N,N-dimethylformamide, vinylene carbonate, tetrahydrofuran, and dimethyl carbonate.
[0098] In some embodiments of the present application, the preparation of the negative electrode layer on the negative electrode current collector using metallic lithium as the material is implemented by the third method or the fourth method.
[0099] The third method comprises the following steps:
[0100] S41: Melting lithium metal and applying it on the surface of the negative electrode current collector,
[0101] The fourth method comprises the following steps:
[0102] S42: depositing lithium metal on the surface of the negative electrode current collector by vacuum evaporation.
[0103] It is easy to understand that when the negative electrode layer is prepared through step S41, the thickness of the negative electrode layer can be adjusted by scraping the surface of the negative electrode layer.
[0104] It is easy to understand that when the negative electrode layer is prepared through step S42, the thickness of the negative electrode layer is regulated by the time and temperature of vacuum evaporation.
[0105] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to industry standards. If there is no corresponding industry standard, then the conditions recommended by the manufacturer are followed.
[0106] Example 1
[0107] First, this embodiment provides an ultra-thin flexible lithium battery, wherein the ultra-thin flexible lithium battery comprises:
[0108] Positive electrode current collector;
[0109] positive electrode layer;
[0110] A solid electrolyte layer, wherein the thickness of the solid electrolyte layer is 25 um;
[0111] A negative electrode layer, wherein the material of the negative electrode layer is lithium metal;
[0112] Negative electrode current collector.
[0113] The solid electrolyte is lithium lanthanum zirconium titanium oxide.
[0114] The negative electrode layer is a lithium metal film, and the thickness of the lithium metal film is 15 um.
[0115] The positive electrode active material of the positive electrode layer is Ni90, and the thickness of the positive electrode layer is 60 um.
[0116] The positive electrode current collector is a composite aluminum foil current collector, and the thickness of the positive electrode current collector is 10 um.
[0117] The negative electrode current collector is a composite copper foil current collector, and the thickness of the negative electrode current collector is 8 um.
[0118] Subsequently, the preparation method of the ultra-thin flexible lithium battery in this embodiment comprises the following steps:
[0119] Providing a positive electrode active material, a binder, and a conductive agent, and uniformly mixing the positive electrode active material, the binder, and the conductive agent in a mass ratio of 96:2:2 to obtain a positive electrode material;
[0120] Spraying the positive electrode material onto the positive electrode current collector to form a positive electrode layer;
[0121] The solid electrolyte and the solvent are mixed by stirring and ultrasonication to obtain an electrolyte slurry, wherein the solvent is tetrahydrofuran;
[0122] Spraying the electrolyte slurry onto the positive electrode layer, and regulating the thickness of the solid electrolyte by controlling the number of spraying times;
[0123] Roll-pressing the solid electrolyte to obtain a solid electrolyte layer;
[0124] Melting lithium metal and applying it on the surface of the negative electrode current collector to form a negative electrode layer;
[0125] The negative electrode layer is laminated to the solid electrolyte layer to obtain the ultra-thin flexible lithium battery.
[0126] Wherein, the conductive agent is Ketjen black and the binder is polytetrafluoroethylene.
[0127] Example 2
[0128] First, this embodiment provides an ultra-thin flexible lithium battery, wherein the ultra-thin flexible lithium battery comprises:
[0129] Positive electrode current collector;
[0130] positive electrode layer;
[0131] A solid electrolyte layer, wherein the thickness of the solid electrolyte layer is 22 um;
[0132] A negative electrode layer, wherein the material of the negative electrode layer is lithium metal;
[0133] Negative electrode current collector.
[0134] The solid electrolyte is lithium germanium phosphorus sulfide.
[0135] The negative electrode layer is a lithium metal film, and the thickness of the lithium metal film is 8 um.
[0136] The positive electrode active material of the positive electrode layer is Ni90, and the thickness of the positive electrode layer is 58 um.
[0137] The positive electrode current collector is a composite aluminum foil current collector, and the thickness of the positive electrode current collector is 10 um.
[0138] The negative electrode current collector is conductive carbon paper, and the thickness of the negative electrode current collector is 6 um.
[0139] Subsequently, the preparation method of the ultra-thin flexible lithium battery in this embodiment comprises the following steps:
[0140] Providing a positive electrode active material, a binder, and a conductive agent, and uniformly mixing the positive electrode active material, the binder, and the conductive agent in a mass ratio of 96:2:2 to obtain a positive electrode material;
[0141] Spraying the positive electrode material onto the positive electrode current collector to form a positive electrode layer;
[0142] The solid electrolyte and the solvent are mixed by stirring and ultrasonication to obtain an electrolyte slurry, wherein the solvent is dimethyl carbonate;
[0143] Applying the electrolyte slurry onto the positive electrode layer by hot solvent casting, and regulating the thickness of the solid electrolyte by scraping the solid electrolyte;
[0144] Roll-pressing the solid electrolyte to obtain a solid electrolyte layer;
[0145] Depositing lithium metal on the surface of the negative electrode current collector by vacuum evaporation to form a negative electrode layer;
[0146] The negative electrode layer is laminated to the solid electrolyte layer to obtain the ultra-thin flexible lithium battery.
[0147] The conductive agent is graphene. The binder is polytetrafluoroethylene.
[0148] Comparative Example 1
[0149] The only difference between this comparative example and Example 1 is that the thickness of the solid electrolyte layer is 45 um.
[0150] The details are as follows:
[0151] First, this comparative example provides an ultra-thin flexible lithium battery, wherein the ultra-thin flexible lithium battery comprises:
[0152] Positive electrode current collector;
[0153] positive electrode layer;
[0154] A solid electrolyte layer, wherein the thickness of the solid electrolyte layer is 45 μm;
[0155] A negative electrode layer, wherein the material of the negative electrode layer is lithium metal;
[0156] Negative electrode current collector.
[0157] The solid electrolyte is lithium lanthanum zirconium titanium oxide.
[0158] The negative electrode layer is a lithium metal film, and the thickness of the lithium metal film is 15 um.
[0159] The positive electrode active material of the positive electrode layer is Ni90, and the thickness of the positive electrode layer is 60 um.
[0160] The positive electrode current collector is a composite aluminum foil current collector, and the thickness of the positive electrode current collector is 10 um.
[0161] The negative electrode current collector is a composite copper foil current collector, and the thickness of the negative electrode current collector is 8 um.
[0162] Subsequently, the preparation method of the ultra-thin flexible lithium battery in this comparative example comprises the following steps:
[0163] Providing a positive electrode active material, a binder, and a conductive agent, and uniformly mixing the positive electrode active material, the binder, and the conductive agent in a mass ratio of 96:2:2 to obtain a positive electrode material;
[0164] Spraying the positive electrode material onto the positive electrode current collector to form a positive electrode layer;
[0165] The solid electrolyte and the solvent are mixed by stirring and ultrasonication to obtain an electrolyte slurry, wherein the solvent is tetrahydrofuran;
[0166] Spraying the electrolyte slurry onto the positive electrode layer, and regulating the thickness of the solid electrolyte by controlling the number of spraying times;
[0167] Roll-pressing the solid electrolyte to obtain a solid electrolyte layer;
[0168] Melting lithium metal and applying it on the surface of the negative electrode current collector to form a negative electrode layer;
[0169] The negative electrode layer is laminated to the solid electrolyte layer to obtain the ultra-thin flexible lithium battery.
[0170] Wherein, the conductive agent is Ketjen black and the binder is polytetrafluoroethylene.
[0171] Comparative Example 2
[0172] The difference between this comparative example and Example 1 is only that:
[0173] The only difference between this comparative example and Example 1 is that the thickness of the solid electrolyte layer is 8 um.
[0174] The details are as follows:
[0175] First, this comparative example provides an ultra-thin flexible lithium battery, wherein the ultra-thin flexible lithium battery comprises:
[0176] Positive electrode current collector;
[0177] positive electrode layer;
[0178] A solid electrolyte layer, wherein the thickness of the solid electrolyte layer is 8 um;
[0179] A negative electrode layer, wherein the material of the negative electrode layer is lithium metal;
[0180] Negative electrode current collector.
[0181] The solid electrolyte is lithium lanthanum zirconium titanium oxide.
[0182] The negative electrode layer is a lithium metal film, and the thickness of the lithium metal film is 15 um.
[0183] The positive electrode active material of the positive electrode layer is Ni90, and the thickness of the positive electrode layer is 60 um.
[0184] The positive electrode current collector is a composite aluminum foil current collector, and the thickness of the positive electrode current collector is 10 um.
[0185] The negative electrode current collector is a composite copper foil current collector, and the thickness of the negative electrode current collector is 8 um.
[0186] Subsequently, the preparation method of the ultra-thin flexible lithium battery in this comparative example comprises the following steps:
[0187] Providing a positive electrode active material, a binder, and a conductive agent, and uniformly mixing the positive electrode active material, the binder, and the conductive agent in a mass ratio of 96:2:2 to obtain a positive electrode material;
[0188] Spraying the positive electrode material onto the positive electrode current collector to form a positive electrode layer;
[0189] The solid electrolyte and the solvent are mixed by stirring and ultrasonication to obtain an electrolyte slurry, wherein the solvent is tetrahydrofuran;
[0190] Spraying the electrolyte slurry onto the positive electrode layer, and regulating the thickness of the solid electrolyte by controlling the number of spraying times;
[0191] Roll-pressing the solid electrolyte to obtain a solid electrolyte layer;
[0192] Melting lithium metal and applying it on the surface of the negative electrode current collector to form a negative electrode layer;
[0193] The negative electrode layer is laminated to the solid electrolyte layer to obtain the ultra-thin flexible lithium battery.
[0194] Wherein, the conductive agent is Ketjen black and the binder is polytetrafluoroethylene.
[0195] Related experiments and effect data:
[0196] The ultra-thin flexible lithium batteries of Examples 1-2 and Comparative Examples 1-2 were subjected to charge and discharge tests, and the first coulombic efficiency and the first discharge specific capacity were recorded. The results are shown in Table 1:
[0197] Table 1
[0198] First coulombic efficiency (%) First discharge specific capacity (mAh / g) Example 1 84.07 204.36 Example 2 83.48 198.77 Comparative Example 1 75.32 173
[0199] Table 1 does not record the test data of Comparative Example 2 because there is a micro-short circuit phenomenon in Comparative Example 2. This may be because the thickness of the solid electrolyte layer is too thin, causing it to be pierced by lithium dendrites, thereby causing a micro-short circuit. Figure 2 is the charge and discharge curve of Comparative Example 2, Figure 2 It can be clearly seen that a micro-short circuit occurred in the ultra-thin flexible lithium battery of Comparative Example 2.
[0200] As can be seen from Table 1, the first coulombic efficiency and the first discharge specific capacity of Comparative Example 1 are significantly reduced compared with Examples 1 and 2. It is speculated that this is due to the excessive thickness of the solid electrolyte layer.
[0201] The ultra-thin flexible lithium battery of Example 1 and Comparative Example 1 was further subjected to an AC impedance test. The results are as follows: Figure 3 . Figure 3 The AC impedance spectra of the ultra-thin flexible lithium battery of Example 1 and Comparative Example 1 are shown in FIG. Figure 1 It can be seen that the impedance of the ultra-thin flexible lithium battery in Example 1 is only 44.3Ω, while the impedance of the ultra-thin flexible lithium battery in Comparative Example 1 is only 183.4Ω, which indicates that the battery impedance in Comparative Example 1 is significantly increased due to the increase in the thickness of the solid electrolyte layer.
[0202] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.
[0203] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present application specification, the terms "including", "comprising", etc. refer to "including but not limited to". Moreover, the terms "including", "comprising" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or equipment including a series of elements not only includes those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or equipment. In the absence of further restrictions, the elements defined by the sentence "including..." do not exclude the existence of other identical elements in the process, method, article or equipment including the elements. In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of associated objects, indicating that there can be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. For the association relationship of more than three associated objects described by "and / or", it means that any one of these three associated objects can exist alone, or any at least two of them exist at the same time. For example, for A, and / or B, and / or C, it can be represented that any one of A, B, and C exists alone, or any two of them exist at the same time, or three of them exist at the same time. In this article, "at least one" refers to one or more, and "multiple" refers to two or more. "At least one", "the following at least one (individual)" or similar expressions refer to any combination of these items, including any combination of single (individual) or plural (individual). For example, "at least one (individual) of a, b, or c", or "at least one (individual) of a, b, and c", can all represent: a, b, c, ab (i.e. a and b), ac, bc, or abc, wherein a, b, and c can be single or multiple, respectively.
[0204] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. An ultra-thin flexible lithium battery, characterized in that: The ultra-thin flexible lithium battery comprises: Positive electrode current collector; positive electrode layer; A solid electrolyte layer, wherein the thickness of the solid electrolyte layer is 10 to 40 μm; A negative electrode layer, wherein the material of the negative electrode layer is lithium metal; Negative electrode current collector.
2. The ultra-thin flexible lithium battery according to claim 1, characterized in that: The solid electrolyte is a ceramic electrolyte or a composite electrolyte.
3. The ultra-thin flexible lithium battery according to claim 2, characterized in that: The ceramic electrolyte is at least one of lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium titanium oxide, lithium phosphorus sulfur chloride, and lithium germanium phosphorus sulfur.
4. The ultra-thin flexible lithium battery according to claim 3, characterized in that: The material of the composite electrolyte includes the ceramic electrolyte and also includes at least one of polyethylene oxide, polyvinyl alcohol and polyvinylidene fluoride.
5. The ultra-thin flexible lithium battery according to claim 1, characterized in that: The negative electrode layer is a lithium metal film, and the thickness of the lithium metal film is 5 to 35 um; and / or, The positive electrode active material of the positive electrode layer is at least one of lithium cobalt oxide, ternary positive electrode material, lithium nickel manganese oxide, lithium-rich manganese-based material, lithium titanate, sodium vanadium fluorophosphate, sodium vanadium phosphate, and Prussian blue; and / or, The thickness of the positive electrode layer is 55-65um; The positive electrode current collector is a composite aluminum foil current collector; and / or, The thickness of the positive electrode current collector is 9 to 12 um; and / or, The negative electrode current collector is any one of copper foil, composite copper foil current collector and conductive carbon paper; and / or, The thickness of the negative electrode current collector is 6-10 um.
6. The method for preparing an ultra-thin flexible lithium battery according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: Providing a positive electrode active material, a binder, and a conductive agent, and uniformly mixing the positive electrode active material, the binder, and the conductive agent to obtain a positive electrode material; Disposing the positive electrode material on the positive electrode current collector to form a positive electrode layer; After a solid electrolyte is disposed on the positive electrode layer, the solid electrolyte is subjected to a roll-pressing process to obtain a solid electrolyte layer; Using metallic lithium as material to prepare a negative electrode layer on a negative electrode current collector; The negative electrode layer is laminated to the solid electrolyte layer to obtain the ultra-thin flexible lithium battery.
7. The method for preparing an ultra-thin flexible lithium battery according to claim 5, characterized in that: The positive electrode active material, the binder and the conductive agent are mixed uniformly, and the mass ratio of the positive electrode active material, the binder and the conductive agent is 96:2:
2.
8. The method for preparing an ultra-thin flexible lithium battery according to claim 5, characterized in that: The positive electrode material is arranged on the positive electrode current collector, and the positive electrode material is arranged on the positive electrode current collector by any one method of spraying, deposition, and coating.
9. The method for preparing an ultra-thin flexible lithium battery according to claim 5, characterized in that: The solid electrolyte is arranged on the positive electrode layer, and the solid electrolyte is arranged on the positive electrode layer by the first method or the second method, The first method comprises the following steps: Mixing the solid electrolyte with a solvent to obtain an electrolyte slurry; The electrolyte slurry is sprayed onto the positive electrode layer, and the thickness of the solid electrolyte is regulated by controlling the number of spraying times. The second method comprises the following steps: Mixing the solid electrolyte with a solvent to obtain an electrolyte slurry; The electrolyte slurry is coated on the positive electrode layer by hot solvent casting, and the thickness of the solid electrolyte is regulated by scraping the solid electrolyte.
10. The method for preparing an ultra-thin flexible lithium battery according to claim 5, characterized in that: The method of preparing a negative electrode layer on a negative electrode current collector using metallic lithium as a material is implemented by the third method or the fourth method. The third method comprises the following steps: The lithium metal is melted and applied to the surface of the negative electrode current collector. The fourth method comprises the following steps: Lithium metal is deposited on the surface of the negative electrode current collector by vacuum evaporation.
Citation Information
Patent Citations
Ultrathin flexible lithium ion battery and preparation method thereof
CN111029657A
Solid-state lithium battery and preparation method thereof
CN112421103A
Composite electrolyte film for all-solid-state lithium metal negative electrode battery, preparation method of composite electrolyte film and all-solid-state sulfide lithium ion battery comprising composite electrolyte film
CN112599846A
Solid-state lithium battery and preparation method thereof
CN113745636A
Pole piece and preparation method thereof, battery and preparation method thereof, and solid-state battery
CN117038862A
